The Effect of Using Genially Assisted Learning Media on Pancasila Education Lessons for Elementary Students - Elly Sukmanasa; R. Teti Rostikawati; Muhammad Hadad (FKIP UNIVERSITAS PAKUAN, 2024)
This research is based on the background of students’ results in pancasila lessons which has still low in learning outcome caused by the lack of effective use of learning media. This study aims to determine the difference in learning outcomes between classes that use Genially learning media and classes that do not use it, as well as to determine the difference in the improvement of student learning outcomes in pancasila Education subjects, especially the material of rights and obligations, in class fourth grader at private elementary school, Bogor. This study used a quasi-experimental method with a nonequivalent control group design. The research subjects were divided into two classes, experimental class consisting of 29 students, and control class consisting of 25 students. Written tests and multiple-choice questions are the test that as research instruments for taking the data. Based on data analysis, it shows there is significant differences in posttest results between students who use genially learning media and students who do not use it. From these data, it can be concluded that genially learning media has a significant effect on student learning outcomes and can be used as an effective alternative learning media for teachers in learning pancasila Education.